2023
DOI: 10.1371/journal.pgph.0000902
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ access to and acceptance of community-based hepatitis C testing and treatment in Myanmar: A mixed-method study

Abstract: Hepatitis C (HCV) infection elimination in low- and middle-income countries requires decentralised HCV services to increase testing and linkage to care. The CT2 Study investigated patients’ views of access to and acceptance of two community-based HCV care models in Myanmar using a mixed-methods approach. Point-of-care HCV testing and general practitioner-initiated HCV treatment were provided at two community clinics in Yangon, Myanmar–the Burnet Institute’s (BI) clinic focused on people who inject drugs (PWID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This can easily be resolved in any future expanded roll-out, and confirmed through annual audits of patient experience at each site. The likely barrier of cost to starting treatment is supported by qualitative findings on acceptability and accessibility of a community-based hepatitis C testing and treatment program in Yangon, where participants described their reluctance to access treatment previously as they had been told by their networks of high treatment costs at both public and private health centres in Yangon and elsewhere in Myanmar [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can easily be resolved in any future expanded roll-out, and confirmed through annual audits of patient experience at each site. The likely barrier of cost to starting treatment is supported by qualitative findings on acceptability and accessibility of a community-based hepatitis C testing and treatment program in Yangon, where participants described their reluctance to access treatment previously as they had been told by their networks of high treatment costs at both public and private health centres in Yangon and elsewhere in Myanmar [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative work from Vietnam outlined the various barriers to seeking care for viral hepatitis, including limited and/or incorrect understanding of how they acquired hepatitis C, lack of trust in the local healthcare system to provide appropriate treatment, difficulty reaching care in centralised hospitals, challenges navigating insurance schemes to cover treatment, and cost of testing and treatment [ 19 ]. In addition, recent qualitative work assessing the acceptability of a community-based model of care in Yangon, Myanmar found that flexible appointment scheduling, short wait times and rapid return of results increased the clinic’s accessibility [ 20 ].…”
Section: Introductionmentioning
confidence: 99%